Pengaruh Kualitas Pelayanan dan Prasarana Pendidikan Terhadap Kepuasan Peserta Didik Pada MTs An-Nizhomiyah - septi, ade; Hidayat, Aris (STIE Tri Bhakti, 2024)
This study discusses the Effect of Service Quality and Educational Infrastructure on Student Satisfaction at MTs An-Nizhomiyah. Using quantitative methods with data obtained by giving questionnaires to 74 learners as respondents. This study aims to determine simultaneously whether the quality of service and the education market affect student satisfaction. The hypothesis carried out is that it is suspected that there is an influence on the quality of educational services and infrastructure on the satisfaction of MTs An-Nizhomiyah students. By using the SPSS analysis test tool, the value in the Model Summary table obtained an R value of 0.746, meaning that it shows a strong relationship between the quality of service and educational infrastructure to student satisfaction. R square is a coefficient of determination that shows the percentage of influence of service quality and educational infrastructure on student satisfaction. The R square value of 0.557 shows that the influence of the quality of educational services and infrastructure together (simultaneously) on student satisfaction. The regression equation formed Y = 6.332 + 0.700 X1 + 0.133 X2 a positive sign means that if the quality of service (X1) and Educational Infrastructure (X2) is improved, it can increase student satisfaction in MTs An-Nizhomiyah (Y).